Role of Media and Judiciary in Public Policy Making in Pakistan: Evidence from Suo Moto Cases based on Media Reports - CHAUDHRY, Mr. MUHAMMAD ASAD; HUSSAIN, Dr. SHAHZAD; HUSSAIN, Dr. FIAZ (The journal of contemporary issues in business and government, 2021)
The role of mass media in policy agenda setting has been considered by an array of researchers. The mass media is not sole factor behind the policy agenda, but it is an important factor among several others. The agenda-setting theory assumes that the media possess the capability to relocate their agenda to the public agenda. Judiciary in Pakistan also seem to be influenced by the agenda-setting function of mass media. The study aims to examine the indirect influence of mass media on public policy by critically analysing the influence of judicial interventions in the form of suo motu on policy making in Pakistan. The time period of the study ranges from 2008 to 2013. The unit of analysis is a single case based on sou motu action taken by the Supreme Court of Pakistan (SCP). All the suo motu actions taken by the SCP based on media reports during the time period have been analysed. The data have been collected from the archives of the SCP and by overviewing the original court files of the cases. The contents analysis reveals that the SCP taken total 90 suo motu cases during the period, and out of these cases, 56 cases were based on media reports. The study further analyses the decisions in these cases influencing the policy making in Pakistan. The findings reveal that 19 court cases based on media reports have influenced the public policy making in Pakistan.